IMPLEMENTASI SISTEM PEMBAYARAN TIKET DENGAN E-MONEY (BRIZZI) PADA PT. ASDP (Studi Pada Pelabuhan Penyeberangan Bolok Kupang) - Jefriyantho Senmalai; Fransina W. Ballo; Cicilia A. Tungga (Universitas Udayana, 2024)
Implementation of a ticket payment system is a system that includes regulations, contracts/agreements, operational facilities, and technical mechanisms used for delivering, validating and receiving ticket payment instructions, as well as fulfilling payment obligations through the exchange of